(3GNJUGU GdeMceI GdLfGFjI GdOhdjI (B/ s - (3YdG YRJ YHOGdeMSfs; (3WGQb GMeO aJMi SQhQ s; (3eCehf eMeO SdGeI s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2007)
(3YQVJ ajg dJLGQH GdbVGA GdLfGFi GdOhdi GdJi SHbJ GdeMceI GdLfGFjI GdOhdjI hYGUQJgG hNdUJ Gdi MGLI deLJeY Gdhdi Gdi eMceI LfGFjI OhdjI OGFeI heMGjOI (B: (3JLfHG ddYOGdI GdGfJbGFjI Gh GdeSjSSI GdHGH GdGhd GNJUGU GdeMceI GdMfGFjI GdOhdjI hbO LGA ai KdGKI aUhd YQVJ ai GdaUd GdGhd dGNJUGU GdeMceI ef MjK GdehVhY ceG YQJ ai GdaUd GdKGfi dGNJUGU GdeMceI ef MjK GdGTNGU (B: (3hai GdKGdK JfGhdJ GNJUGUgG ef MjK GdReGfs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2007s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B335-360s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GNJUGU GdeMceI GdLfGFjI GdOhdjIs; (3GdeMceI GdLfGFjI GdOhdjIs; (3GdhdGjIs; (3GdbVGA GdLfGFi GdOhdis; (3LQjeI GdEHGOI GdLeGYjIs; (3LQGFe GdMQHs; (3LQjeI GdYOhGfs; (3eSFhdjI GdbGFO GdYScQis; (3GNJUGU GdbGFO ZjQ GdYScQis; (3GNJUGU GdQFjS GdYScQis; (3MLjI CMcGe GdeMceI GdLfGFjI GdOhdjIs; (3ELQGAGJ JMQjc GdOYhi CeGe GdeMceIs; (3QSGFd LGeYjI s -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs